TNF-<svg style="vertical-align:-0.216pt;width:14.1125px;" id="M1" height="10.725" version="1.1" viewBox="0 0 14.1125 10.725" width="14.1125" xmlns:xlink="http://www.w3.org/1999/xlink" xmlns="http://www.w3.org/2000/svg"> <g transform="matrix(.022,-0,0,-.022,.062,10.4)"><path id="x1D736" d="M505 450h125l-163 -259q-1 -4 -1 -12q0 -19 1 -23q9 -98 41 -98q36 0 58 76l24 -7q-34 -139 -121 -139q-32 0 -57.5 24t-31.5 55q-72 -77 -181 -77q-73 0 -114 44t-41 124q0 118 79 210q79 93 197 93q51 0 86 -27t50 -71zM369 281q0 141 -62 141q-43 0 -95 -84 q-52 -82 -52 -195q0 -50 15 -83t42 -33q35 0 79 57q43 58 67 121q6 35 6 76z" /></g> Regulates Natriuretic Peptides and Aquaporins in Human Bronchial Epithelial Cells BEAS-2B - Mezzasoma, Letizia; Cagini, Lucio; Antognelli, Cinzia; Puma, Francesco; Pacifico, Eugenio; Talesa, Vincenzo Nicola (Mediators of Inflammation, 2013)
Postoperative-fluid retention is a severe complication frequently reported in patients undergoing major surgical procedures. The complex network of molecules involved in such a severe surgery-induced condition remains poorly understood. Inflammation has been proposed among the various causes of fluid retention. Since TNF-α is one of the main proinflammatory cytokine initially released after major surgery, it is reasonable to assume its involvement in fluid overload. Here, we showed that TNF-α selectively regulates key molecules involved in fluids balance, such as natriuretic peptides (NPs) and aquaporins, in human bronchial epithelial cells BEAS-2B. In particular, we found that TNF-α induced a decrease of arial natriuretic peptide, natriuretic peptide receptor-1, aquaporin-1 and aquaporin-5 and an increase of brain natriuretic peptide with a different involvement of nuclear factor-κB and mitogen-activated protein kinases signaling pathway activation. Moreover, the observed changes in NPs expression, demonstrate inflammation as an additional cause of brain natriuretic peptide elevation, adding an important piece of information in the novel area of study regarding NPs and inflammation. Finally, we suggest that inflammation is one of the mechanisms of Aquaporin-1 and aquaporin-5 expression regulation. Therefore, in this exploratory study, we speculate that TNF-α might be involved in postoperative-fluid retention related to major surgery.